Pengaruh Motivasi Kerja, Komunikasi dan Lingkungan Kerja Non Fisik Terhadap Kinerja Driver Maxim di Kediri - Mustikasari, Galuh Ajeng; Akbar, Taufik; Syahputra, Erwin (Populer: Jurnal Penelitian Mahasiswa, 2023)
This research is motivated by a company engaged in the field of online transportation, because in the company of human resources is a determinant of success. The purpose of this study to explain the effect of work motivation, communication and non-physical work environment on employee performance. The study was conducted on Maxim drivers in Kediri. The research method used is quantitative method. This study used purposive sampling technique. The population of this study was 1000 drivers and the sample used was 69 respondents. The data analysis techniques used are multiple linear regression analysis, coefficient of determination (R2), t test and f test. The results obtained by this study concluded that work motivation has a positive and insignificant effect on performance. Communication has a negative and insignificant effect on performance. The non-physical work environment has a positive and significant effect on performance. Simultaneously work motivation, communication and non-physical work environment have a positive and significant effect on performance.